Ethical Aspects in Cyber Security - Hamburg, Ileana; Grosch, Kira Rosa (Archives of Business Research, 2017)
Cyber Security (CS) industry increases every year employment chances as well as the requirements at staff working in this field and at education. In January 2013, Cyber Security Strategy has been prepared by European Commission and it is decided that vocational and academic trainings in cyber security field should be improved also by including of topics in the curriculum like ethical, social and psychological ones. Ethics helps to distingue right from wrong, and good from bad. It analyzes the morality of human behaviors, policies, laws and social structures, in this paper we consider Ethic aspects in Information Security (IS)/ Cyber security (CS) being one of our research and development domain. A European project aimed at improving CS courses and knowledge of students in Ethics is presented.